A hybrid neural network/rule-based technique for on-line gesture and hand-written character recognition - Craven, Michael P.; Curtis, K. Mervyn; Hayes-Gill, Barrie H.; Thursfield, C.D. (1997)
A technique is presented which combines rule-based and neural network pattern recognition methods in an integrated system in order to perform learning and recognition of hand-written characters and gestures in realtime.